The association guide to going global : new strategies for a changing economic landscape - Worth, Steven M. (Hoboken, N.J. : Wiley, 2010)
Why going global is critical-and inevitable-for your association's growth and survival. Multiple case studies of associations that have entered the global arena will be included. The Association Guide to Going Global demonstrates how many associations have used globalization to their advantage, finding that increasing their reach and influence on an international scale has allowed their organizations continued success.: Underscores how the advantages of changes outweigh the risks; How adapting to new market trends is an act that cannot, and should not, be avoided; Offers a problem-solution gui.
The Association Guide to Going Global: New Strategies for a Changing Economic Landscape; Contents; Foreword; Introduction; Chapter 1: Why Go Global?; Chapter 2: Common Problems in the Global Arena; Chapter 3: The Structure of the Globalized Association; Chapter 4: Funding and Financing; Chapter 5: Language and Culture; Chapter 6: Endeavors in Specific Countries; Chapter 7: Successes and Failures: Key Ingredients to Globalization Success; Chapter 8: Final Thoughts on Truly Becoming Global; About the Author; Index.
Print version record.
English.
John Wiley and Sons
Keywords: Trade associations; Associations, institutions, etc; International business enterprises; Globalization; Societies; Associations professionnelles; Associations; Entreprises multinationales; Mondialisation; globalism; BUSINESS & ECONOMICS -- International -- General; Associations, institutions, etc; Globalization; International business enterprises; Trade associations